Respuesta :

2

x

+

3

y

=

1

2

x

+

3

y

=

1

,

2

x

3

y

=

1

-

2

x

-

3

y

=

-

1

Solve for

y

y

in the second equation.

Tap for more steps...

2

x

+

3

y

=

1

2

x

+

3

y

=

1

y

=

2

x

3

+

1

3

y

=

-

2

x

3

+

1

3

Replace all occurrences of

y

y

with the solution found by solving the last equation for

y

y

. In this case, the value substituted is

2

x

3

+

1

3

-

2

x

3

+

1

3

.

2

x

+

3

(

2

x

3

+

1

3

)

=

1

2

x

+

3

(

-

2

x

3

+

1

3

)

=

1

y

=

2

x

3

+

1

3

y

=

-

2

x

3

+

1

3

Solve for

x

x

in the first equation.

Tap for more steps...

Always true

y

=

2

x

3

+

1

3

y

=

-

2

x

3

+

1

3

Remove any equations from the system that are always true.

y

=

2

x

3

+

1

3

y

=

-

2

x

3

+

1

3

The solution can be shown in both point and equation forms.

Point Form:

(

x

,

2

x

3

+

1

3

)

(

x

,

-

2

x

3

+

1

3

)

Equation Form:

x

=

x

y

=

2

x

3

+

1

3


ACCESS MORE